Advanced High Strength Steels: Improved Properties by Design of Textures and Microstructures - Castro-Cerda, F (Institute of Physics Publishing, 2017)
Texture and microstructure formation during annealing of a 75% cold rolled AHS steel, reheated at a rate of 10°C/s to ∼3000°C/s were studied with the purpose to investigate the interaction between the recrystallization and the austenite formation as well as the possibility of grain refinement. It was found that at ultra-high heating rates, the bcc-fcc phase transformation starts before the completion of recrystallization and the deformation texture is partially retained in the samples after annealing. The crystallographic texture observed in the martensitic phase, which is the product of intercritical austenite transformation in as-quenched samples, i.e., after the double α-γ-α transformation, is similar to the initial cold rolling texture, which is an indication for the texture memory effect. After ultra-fast reheating with average reheating rates of 1000°C/s and higher, a significant grain refinement was observed with an average calculated ferrite grain diameter of ∼2 μm. The obtained final ferrite grain size depends significantly on both the reheating temperature and the heating rate. The same effect is observed in 75% cold rolled quenching and partitioning steels for heating rates of 400°C/s, 800°C/s and 1000°C/s. In both cases the combination of fine grains, and weak RD/ND-fiber textures produce an increase of strength and ductility compared to material annealed using a conventional heating rate of ∼10°C/s. © Published under licence by IOP Publishing Ltd.